2016
DOI: 10.1038/srep27905
|View full text |Cite
|
Sign up to set email alerts
|

A general method for parameter estimation in light-response models

Abstract: Selecting appropriate initial values is critical for parameter estimation in nonlinear photosynthetic light response models. Failed convergence often occurs due to wrongly selected initial values when using currently available methods, especially the kind of local optimization. There are no reliable methods that can resolve the conundrum of selecting appropriate initial values. After comparing the performance of the Levenberg–Marquardt algorithm and other three algorithms for global optimization, we develop a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Three model parameters were estimated for the selected two periods estimated using the Levenberg-Marquardt method, implemented in the minpack.lm package [51] in R [47]. The Levenberg-Marquardt method is a widely used algorithm for analyzing non-linear light-response curves [52,53]. NEP sat was calculated with the obtained three parameters and by fixing PAR at 1500 µmol photon m −2 s −1 .…”
Section: Data Anlaysis and Statistical Modelmentioning
confidence: 99%
“…Three model parameters were estimated for the selected two periods estimated using the Levenberg-Marquardt method, implemented in the minpack.lm package [51] in R [47]. The Levenberg-Marquardt method is a widely used algorithm for analyzing non-linear light-response curves [52,53]. NEP sat was calculated with the obtained three parameters and by fixing PAR at 1500 µmol photon m −2 s −1 .…”
Section: Data Anlaysis and Statistical Modelmentioning
confidence: 99%
“…Following the recommendations of Chen et al. (2016), the lower and upper limits of the following parameters in the model: θ (curvature factor), ϕ (quantum yield), A max (light‐saturated rate of gross CO 2 assimilation) and R d (dark respiration) were set at 0, 0, 0, 0 and 1, 1, 100, 100, respectively, during the optimisation process.…”
Section: Methodsmentioning
confidence: 99%
“…Curve fitting was optimised using differential evolution via the 'DEoptim' 2.4-4 (Ardia et al, 2010;Mullen et al, 2011) package in r 3.5.3 (R Development Core Team, 2019). Following the recommendations of Chen et al (2016), the lower and upper limits of the following parameters in the model: θ (curvature factor), ϕ (quantum yield), A max (light-saturated rate of gross CO 2 assimilation) and R d (dark respiration) were set at 0, 0, 0, 0 and 1, 1, 100, 100, respectively, during the optimisation process.…”
Section: Experiments 1: Photosynthetic Capacity and Responsiveness To...mentioning
confidence: 99%
“…It has been shown that the Nonrectangular Hyperbola Model offers greater flexibility compared to the Rectangular Hyperbola Model, attributed to its inclusion of an additional curvature parameter. This enhanced flexibility is particularly advantageous when fitting photosynthetic light response curves for specific species of plants [21] . Additionally, the Modified Rectangular Hyperbola Model for higher plants can reproduce the irradiance response trends of photosynthesis well and for phytoplankton species can obtain close values to the measured data, but the fitted curves exhibited some slight deviations under low intensity of irradiance [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need to test which photosynthetic light response model describes the relationship between light intensity and the rate of photosynthesis in plants in the most accurate manner. Prior researches in model comparison have predominantly concentrated on assessing the goodness of fit (e.g., coefficient of determination) or exploring the trade-off between goodness of fit and model structural complexity (e.g., the Akaike information criterion) [21,22] . However, there remains a comparative dearth in quantifying and comparing the nonlinearity of photosynthetic light response models, despite its potential to provide valuable insights into photosynthetic mechanisms.…”
Section: Introductionmentioning
confidence: 99%